Музей-заповедник "Лудорвай" - Тарануха Галина Владимировна (Удмуртия, 2018)
Экземпляры: (20201007) / Инвентарный номер: 41622 / Цена: / Сис.шифр: 26.89(2=664.1) / Авт.знак: М 90 / ГРНТИ: 39.19 / ББК: 26.89(2=664.1)